FENOMENA LESBIAN YOGYAKARTA SEBUAH FAKTA SOSIAL - Abdul Jalil (Jurnal Kawistara, 2016)
This paper is going to discuss the phenomenon of lesbian Jogja as a social fact. Lesbian behavior is only beginning to be something suitable for consumption by lesbian world, but a decade now, the worldbecomes a product and lesbian public consumption, like it or not there are very real to all of us before and we have to address in the frame is a multicultural society. Another purpose of this paper does not want to look back on how far the phenomenon of lesbians, particularly in the 1980s or when the author was a student of Anthropology in 2005, as an inscription which is still a draft paper for course assignments Sex, Society, and Culture is still very relevant to today’s world, although in fact, when compared with the world Gay, lesbian world more closed. The method used is descriptive analysis, through the later cases seen in theory and then interpreted. The result of this thinking , states that the discourse of “ lesbian “ in the era of technology is not new and taboo. Today, the lesbian world is very open and acceptable in all walks of life. Lesbian world considered marginal. This assessment is different from the standpoint of psychological, social, cultural, and religious. In the context of a patriarchal tradition, always puts the position of women as subordinate to men. Thus , in order to be accepted in the lesbian community, especially the middle of the environment, whether family, friends hanging out, and the others, then lesbians must take an active role in various social activities, social organizations, even religious.